Cotard’s Syndrome: Two Cases of Self-Starvation - Teixeira, Bruno Gonçalves (2015)
Background: Cotard´s syndrome is a relatively rare condition characterized by various degrees of nihilist delusions, often in the form of self-negation. Aims: To report two cases of Cotard’s syndrome associated with self-starvation and to review the concept and clinical features of the condition. Methods: Two clinical cases of the syndrome were obtained and a literature review of the theme was shortly surveyed. Results and Conclusions: The first case is about a woman who believed that her esophagus and stomach were glued. She was treated with sertraline, mirtazapine and risperidone with good results. The second case describes a man who believed his throat was burnt and he had no internal organs. He was treated with clomipramine and risperidone showing great improvement. This syndrome is a nosological and clinical entity that should not be forgotten. It is essential to provide an urgent and adequate therapeutic approach to these patients.